Exploring the structure of the shot effectiveness model for elite table tennis players - Qing Yang; Mu-zi Li; Zheng Zhou; Hui Zhang (BMC, 2023)
Abstract Background Currently, technical and tactical analysis has become an indispensable task for sport in many countries. Many studies analysed players' specific technical and tactical factors, but it is rare to quantitatively analyse the importance of table tennis players' shot effectiveness. This is the first study to propose the new concept of "shot effectiveness model", and the purpose of this study is to explore the structure of the shot effectiveness model for elite table tennis, including the importance degree of shot effectiveness, and the relationship between them. Methods 258 matches were selected between the top 50 players in the world from 2019 to 2021 as samples. Multiple regression analysis was used to obtain the standard regression coefficients and game simulation, and the total decision coefficient (TDC) was used to evaluate the importance degrees of shot effectiveness (SE) on match results. Results (1) There was little difference in the importance degree of each shot effectiveness between men and women players. (2) The importance degree of the first and third shots (SE1), the second and fourth shots (SE2), the fifth and after shots (SE3), and the sixth and after shots (SE4) for both men and women players account for approximately 25%, 35%, 22%, and 16% respectively. (3) There was little difference in the importance degree of each shot effectiveness between Chinese women players and women players from other countries and regions with the same importance order of SE2 > SE1 > SE3 > SE4. However, the structure of the shot effectiveness model for men players was quite different from that for women players. (4) There is a compensation effect between shot effectiveness of table tennis players, and the total evaluation score of 12 and 13 is the dividing line for success or failure in both men and women matches. Conclusions TDC could well reflect the important degrees of each shot effectiveness in various ways on winning probability in table tennis matches. And this study compared the importance of several types of players' performance on the probability of winning a match. In addition, we found that there is a compensation effect between shot effectiveness of table tennis players, and the magnitude of this effect will vary according to the type and level of shot effectiveness.